Addressing Antimicrobial Resistance: An Overview of Priority Actions to Prevent Suboptimal Antimicrobial Use in Food-Animal Production - Lhermie, Guillaume; Gröhn, Yrjö T.; Raboisson, Didier (Frontiers in Microbiology, 2017)
The growing concern regarding emergence of bacteria resistant to antimicrobials and their potential for transmission to humans via animal production has led various authorities worldwide to implement measures to decrease antimicrobial use in livestock production. These measures are influenced by those implemented in human medicine, and emphasize the importance of antimicrobial stewardship, surveillance, infection prevention and control and research. In food producing animals, unlike human medicine, antimicrobials are used to control diseases which cause economic losses. This major difference may explain the failure of the public policies implemented to control antimicrobial usage. Here we first review the specific factors influencing antimicrobial use across the farm animal sector and highlighting the farmers’ decision-making process of antimicrobial use. We then discuss the efficiency of existing regulations implemented by policy makers, and assess the need for alternative strategies, such as substitution between antimicrobials and other measures for infectious disease control. We also discuss the interests of regulating antimicrobial prices. Finally, we emphasize the value of optimizing antimicrobial regimens, and developing veterinary precision medicine to achieve clinical efficacy in animals while limiting negative impacts on public health. The fight against antimicrobial resistance requires both a reduction and an optimization of antimicrobial consumption. The set of actions currently implemented by policy makers does not adequately address the economic interests of farmers’ use of antimicrobials.